Feasibility Analysis of PLN's Mining Electric Vehicle Implementation: A Techno-Economic Study of South Kalimantan Coal Mining and National Energy Policy Implications - Adi, Tri Wahyu; Prihasta, Nurrohman Galih (Journal of Authentic Research, 2026)
The mining sector is one of the largest contributors to carbon emissions in Indonesia, mainly due to the intensive use of diesel- and B40-fueled dump trucks in mining operations. The mandatory implementation of B40 starting January 1, 2025, is expected to reduce dependence on fuel imports and support the national target of achieving Net Zero Emission (NZE) by 2060; however, this policy also increases operational costs for mining companies because the price of B40 is higher than conventional diesel. In this context, the electrification of mining vehicles through the adoption of electric vehicle (EV) dump trucks emerges as a potential solution to simultaneously reduce operational costs and carbon emissions. This study aims to analyze the technical and economic feasibility of transitioning mining dump trucks from diesel/B40 to EV trucks. The research employs a descriptive quantitative method with a case study approach. Technical analysis is conducted to estimate electrical power requirements, fast-charging capacity based on the GB/T standard, and operating load profiles of EV trucks under mining conditions. Economic analysis involves a comparison of operating costs between diesel-based dump trucks and EV trucks, as well as an evaluation of key financial indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), Benefit–Cost Ratio (B/C), and Payback Period. In addition, a strategic analysis is carried out to assess the broader implications of mining electrification for PLN’s business strategy, cost efficiency for mining operators, and alignment with national energy transition objectives. Overall, this study is expected to contribute to policy formulation by providing evidence-based insights on the role of EV trucks in supporting cost-efficient, low-emission mining operations and accelerating Indonesia’s transition toward a more sustainable and decarbonized energy system.